Current application and future pathways of smart older adult care services in China - Xue, Jie (Frontiers in Digital Health, 2025)
The aging problem in China has been more and more severe so that traditional older adult care service models are difficult to meet the growing demands of the older adult population. Smart older adult care, as an emerging service model, integrates artificial intelligence (AI) technologies to provide more personalized, convenient, and safe living services for the older adult. This paper analyzed the applications and development trends of AI in health monitoring and management, smart homes, emotional companionship, and medical services for older adult care and proposed some pathways to foster the healthy development of AI-enabled older adult care services by simplifying technological interfaces, enhancing user experience, strengthening data privacy protections, promoting industry standardization and so on.